PENGUKURAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DOMAIN BAI PADA FUNGSI NON-ERP SOLUTION PT XYZ: MEASUREMENT OF INFORMATION TECHNOLOGY GOVERNANCE USING THE COBIT 5 FRAMEWORK DOMAINS BAI IN NON-ERP SOLUTION FUNCTIONS PT XYZ - Imania, Friska; Halimatul Hidayah, Qori (Jurnal Sistem Informasi dan Bisnis Cerdas, 2024)
This research is conducted to measure and improve the performance of Information Technology (IT) governance using COBIT 5, as well as providing in-depth insight into the factors that affect performance and constraints on the Non-ERP Solution Function. Measurements are made by referring to the Process Assessment Model in COBIT 5 to determine the level of capability. This research aims to determine the obstacles experienced by the Non-ERP Solution in providing centralized services, measure level of capability in implementation IT governance from the current condition (as-is) to the expected condition (to-be) and conduct gap analysis.This research uses the Process Assessment Model (PAM) to measure IT governance capabilities. The research stages refer to the Assessment Process Activities provide in COBIT 5. The measured domain is determined through COBIT 5 mapping against the company''s goals. The data collection method used is a mixed methodology, which includes qualitative and quantitative methods.The obstacles faced by the Non-ERP Solution Function of PT XYZ in providing centralized services are related to consistency in implementation, especially in terms of human resource which sometimes does not follow the established procedures consistently. IT governance measurement shows that the BAI03 process is currently at level 4 (Predictable Process). However, there is a gap in achieving the company''s target that sets level 5 for the process. Keywords: IT Governance, COBIT 5, Capability Level